Applying a digital literacy framework and mapping tool to an occupational therapy curriculum. (5th February 2020) - McKinstry, Carol; Iacono, Teresa; Kenny, Amanda; Hannon, John; Knight, Kaye
Abstract: Introduction: Amidst claims that rapid technological changes in health far outstrip the capabilities of the health workforce, digital literacy is featured in occupational therapy competency standards. However, little attention have been given to the development of digital literacy in entry‐level occupational therapy programmes and the preparation of graduates for digital health. There is a lack of guidance on how universities can demonstrate digital literacy development in occupational therapy students. The aim of this study was to test the usefulness of a digital literacy framework and mapping tool in identifying opportunities for students to develop digital literacy within an entry‐level occupational therapy programme. Methods: Intrinsic case study design was used to test the usefulness of the digital literacy framework and mapping tool. The framework and tool were applied to the curriculum of a large entry‐level Australian occupational therapy programme. Results: Through the process of mapping, key insights were developed on how digital literacy was embedded across the occupational therapy curricula. Limited attention was given to the development of student digital literacy in the early years of the programme. In later years, more opportunities were available to develop digital literacy at basic and intermediate levels. Across the programme, there was limited evidence of the development of advanced digital literacy. Conclusions: The framework and mapping tool were useful in broadening understanding of the concept of digital literacy beyond information communication technologies. The framework and tool can assist those designing or refining occupational therapy curricula to operationalise the notion of digital literacy for practice, and prompt discussion and debate on digital literacy and requirements for students, graduates and occupational therapists in an ever‐changing complex health environment.